Youth Perception of Legislative General Elections in Pidie Regency - Rozaili Rozaili; Zulfikar Zulfikar (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Democracy is a brilliant idea that changes the politics of the world. The emergence of democracy is something that is considered important because it is a political idea containing values that are indispensable as a reference for managing the life of the nation and a good state. Based on the description above, researchers can formulate the problem as follows: 1 ) What is the youth's response to the legislative elections in 2019? 2) What is the level of youth awareness towards the legislative elections in 2019? The approach used in this research is a quantitative approach with descriptive type. A quantitative approach with a descriptive type aims to explain, summarize various conditions, various situations, or various variables that arise in the community that become the object based on what is happening. From the results of the study found 37% of youth did not use their voting rights and 63% used their voting rights. This is the benchmark among young people so apathetic towards the politics that are running in this country. The disappointment that young people get from previous legislators is their benchmark for voting in this election, guided by this research, it will be the biggest disaster for youth in the world of politics. As for the youth who belong to the group chose almost half of them chose because of financial factors and encouragement from others and very few chose according to conscience, For this reason, they chose not to be involved in legislative elections this year, and to take care of more important matters according to them.